Alteration in thiols homeostasis, protein and lipid peroxidation in renal tissue following subacute oral exposure of imidacloprid and arsenic in Wistar rats. (2018) - Mahajan, Lakshay; Verma, Pawan Kumar; Raina, Rajinder; Pankaj, Nrip K.; Sood, Shilpa; Singh, Maninder
Graphical abstract: Highlights: The present study assessed whether imidacloprid (IMI) at NOAEL dose to potentiate the arsenic induced oxidative renal damage in Wistar rats. Elevated renal damage indicators and reduced antioxidant biomarkers following repeated administrations of IMI or arsenic indicate renal damage. Such renal tissue alterations were more pronounced in co-exposed toxicant groups of rats. Study indicating the potentiation of arsenic induced renal damage by IMI in wistar rats. Abstract: The aim of present study was to assess whether No Observed Effect Level (NOEL) of imidacloprid (IMI) potentiates the arsenic induced renal toxicity at its maximum contaminant level in drinking water in Wistar rats. Significant elevation of lipid and protein oxidation with reduced level of total thiols and antioxidant enzymes (catalase, superoxide dismutase, glutathione reductase, glutathione peroxidase and glutathione-s-transferase) in renal tissue may have contributed to increased renal plasma biomarkers (creatinine and blood urea nitrogen) following repeated exposure of IMI and arsenic alone and in-combination. The altered renal biomarkers in co-exposed groups corroborated with histopathological alterations in renal tissue. The observations indicated that altered thiol homeostasis in renal tissue may be associated with increased lipid and protein oxidation in IMI and arsenic administered rats. It is concluded that administration of IMI potentiate the arsenic induced renal damage in Wistar rats.